2014
DOI: 10.1037/a0036264
|View full text |Cite
|
Sign up to set email alerts
|

Once is too much: Conditioned aversion develops immediately and predicts future cocaine self-administration behavior in rats.

Abstract: Rats emit aversive taste reactivity (TR) behavior (i.e., gapes) following intraoral delivery of a cocaine-paired taste cue and greater conditioned aversive TR at the end of training predicts greater drug-seeking and taking. Here, we examined the development of this conditioned aversive TR behavior on a trial by trial basis in an effort to determine when the change in behavior occurs and whether early changes in this behavior can be used to predict later drug-taking. The results show that conditioned aversive T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
(93 reference statements)
3
21
0
Order By: Relevance
“…Kasanetz et al (2010) drew a similar conclusion by measuring persistence in responding during the latter part of the non-drug periods. Finally, Colechio et al (2014) showed that early orofacial responses to a cocaine-paired taste cue could predict later differences in responding for cocaine following a single taste-drug pairing. Vulnerability for addiction, then, can potentially be evidenced very early on and the effect grows with experience, particularly for some rats.…”
Section: Discussionmentioning
confidence: 99%
“…Kasanetz et al (2010) drew a similar conclusion by measuring persistence in responding during the latter part of the non-drug periods. Finally, Colechio et al (2014) showed that early orofacial responses to a cocaine-paired taste cue could predict later differences in responding for cocaine following a single taste-drug pairing. Vulnerability for addiction, then, can potentially be evidenced very early on and the effect grows with experience, particularly for some rats.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs of abuse have both rewarding and aversive effects (Cunningham, 1979; Turenne et al, 1996; Verendeev and Riley, 2011), and it is the balance of these two affective properties that impact their use and abuse (Colechio et al, 2014; Riley et al, 2009; Stolerman, 1985; Wise et al, 1976). One class of drugs only beginning to be examined in this context are the synthetic cathinones (Al-Juhaishi et al, 2012; Busardo et al, 2015; Kalix, 1992; Patel, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Drugs of abuse have both rewarding and aversive effects, and it is the balance of these two affective properties that impact the use and abuse of these compounds (Colechio et al, 2014; Riley et al 2009; Stolerman, 1985; Wise et al, 1976). Understanding this relative balance and the factors that influence it may be critical in predicting vulnerability to the drug’s use and abuse (Cunningham et al, 2009; Riley, 2011).…”
Section: Introductionmentioning
confidence: 99%